The Biological Basis of Physics and the Role of Homeopathy - Hartmann, Michael (Homœopathic Links, 2014)
Efforts have been made to integrate homeopathy into the system of natural sciences. In this article an alternative approach is offered. The very base of physics and mathematics, on which natural sciences are grounded are time, space and number. Since Immanuel Kant they are believed to be a priori given. Alternatively they can be explained as a consequence of life, such that the outside world in the form, as we perceive it, should no longer be considered independent from us as living beings. Having understood the base of physics, homeopathy does not have to be integrated into an existing system of natural sciences, but can be allowed to be more closely connected to the proper origin of physics, which is life itself.
Keywords: Natural philosophy; Physics; Time; Space; Reality